The electrical conductivity of CNT/graphene composites: a new method for accelerating transmission function calculations - Glukhova, Olga E.; Shmygin, Dmitriy S. (Beilstein Journal of Nanotechnology, 2018)
We present a new universal method to accelerate calculations of transmission function and electrical conductance of 2D materials, the supercell of which may contain hundreds or thousands of atoms. The verification of the proposed method is carried out by exemplarily calculating the electrical characteristics of graphene and graphane films. For the first time, we calculated the transmission function and electrical conductance of pillared graphene, composite film of carbon nanotubes (CNTs)/graphene. The electrical conductance of different models of this material was calculated in two mutually perpendicular directions. Regularities in resistance values were found.
Keywords: carbon composites; electronic properties; interpolation; quantum transport; transmission function